Gene organization of DC and DX subregions of the human major histocompatibility complex. - Okada, K (1985)
The DC and DX subregions of the human major histocompatibility complex (MHC) have been cloned from a cosmid library made from a human B-cell line, Priess. The DC subregion, 48 kilobases, includes the DC alpha and DC beta genes. A second DC-like region, the DX subregion, 35 kilobases, contains the DX alpha gene and a newly found beta gene termed DX beta. Since the DC and DX genes are highly homologous in nucleotide sequence, gene size, exon-intron organization, and direction of transcription, the DC and DX subregions were presumably generated by duplication of an ancestral alpha-beta gene pair. Nucleotide sequencing indicates that all four genes have intact coding sequences and promoter regions. Homology between the upstream promoter sequences of these four genes and seven other class II genes at nucleotides -69 to -78 and -98 to -110 highlights these previously described conserved elements. Moreover, a striking conservation of flanking alpha-gene-specific and beta-gene-specific sequences has been observed. Comparison of Southern blots of Priess DNA with DC alpha and DC beta cDNA probes with isolated cosmid clones showed that (i) the human chromosome encodes only two DC alpha-related and two DC beta-related genes, namely, DC alpha, DX alpha, DC beta, and DX beta, and (ii) the DC and DX subregions are homozygous in Priess cells.